2002
DOI: 10.1002/jsfa.1201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harvest time and storage on dietary fibre components in various cultivars of white cabbage (Brassica oleracea var capitata)

Abstract: The effect of harvest time and storage on dietary fibre content and composition was investigated in six cultivars of white cabbage (Brassica oleracea var capitata). Three cultivars were of early maturity type (SW Nordpol, Rolly and Balbro) and three of late maturity type (Predikant, Hanna and Lion). The average total dietary fibre (TDF) content was 241 g kg À1 dry matter (DM) (CV = 13), of which approximately 25% was soluble (CV = 15). The main dietary fibre components were glucose (37%), uronic acid (32%), ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
(26 reference statements)
1
13
0
1
Order By: Relevance
“…Araf and Galp could constitute an individual arabinogalactan or be degradation products from pectic side chains, as suggested elsewhere [34]. The absence of starch was in accordance with results published previously [1], still the resonance at 100.7 could be a-linked Glcp. Based on this, and linkage studies, this polymer could be similar to the glucomannan described by Hua et al Table 1).…”
Section: The Neutral Iec Fractionssupporting
confidence: 84%
See 1 more Smart Citation
“…Araf and Galp could constitute an individual arabinogalactan or be degradation products from pectic side chains, as suggested elsewhere [34]. The absence of starch was in accordance with results published previously [1], still the resonance at 100.7 could be a-linked Glcp. Based on this, and linkage studies, this polymer could be similar to the glucomannan described by Hua et al Table 1).…”
Section: The Neutral Iec Fractionssupporting
confidence: 84%
“…White cabbage is an important vegetable in Scandinavian household [1]. In addition to nutrition, leaves from white cabbage are used in traditional medicine to treat bedsores and inflammation in skin and joints.…”
Section: Introductionmentioning
confidence: 99%
“…The early cabbage variety, Tekila F 1 , contained lower amounts of fibre than the later-maturing cultivars, which was associated with lower levels of cellulose and pectins in the fibre of that cultivar. Studies by Wennberg et al (2002), who analysed several cabbage varieties of different maturity earliness, had also shown that the early cultivars had lower levels of fibre and its fractions in comparison with medium-late and late cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…The relative amounts of the separate constituents of the dietary fibre in fresh cabbage vary and depend on the cultivar, fertilization and harvest date (Sorensen 1984, Elkner 2000. A considerable effect on the changes in fibre content and the size of its fractions in cabbage is shown by the length of the storage period and the method of processing (Elkner 2002, Wennberg et al 2002. Studies by Elkner & Kosson (1995) had revealed that the fermentation process reduced the fibre content in the late cabbage cultivar Kamienna Głowa.…”
Section: Introductionmentioning
confidence: 99%
“…Eating large quantities of carrots even appears to have a constipating effect (Sansone & Sansone, 2012). Some vegetables contain much fibre but this varies according to cultivar, time of harvest and storage; early maturity types or plants harvested before maturity had the least dietary fibre (Wennberg et al, 2002). About 10% of total dietary fibre in cabbage is lost during cooking in boiling water (Wennberg et al, 2003).…”
Section: Fruits and Vegetables; Pectinmentioning
confidence: 99%